Characterization of an inducible C2H2‐type zinc finger transcription factor VuSTOP1 in rice bean (Vigna umbellata) reveals differential regulation between low pH and aluminum tolerance mechanisms. Issue 2 (13th May 2015) - Fan, Wei; Lou, He Qiang; Gong, Yu Long; Liu, Mei Ya; Cao, Meng Jie; Liu, Yu; Yang, Jian Li; Zheng, Shao Jian
Summary The rice bean (Vigna umbellata) root apex specifically secretes citrate through expression activation of Vigna umbellata Multidrug and Toxic Compound Extrusion 1 (VuMATE1) under aluminum (Al3+) stress. However, the underlying mechanisms regulating VuMATE1 expression remain unknown. We isolated and characterized a gene encoding Sensitive to Proton Rhizotoxicity1 (STOP1)‐like protein, VuSTOP1, from rice bean. The role of VuSTOP1 in regulating VuMATE1 expression was investigated using the yeast one‐hybrid assay. We characterized the function of VuSTOP1 in Al3 + ‐ and H+‐tolerance using in planta complementation assays. We demonstrated that VuSTOP1 has transactivation potential. We found that VuSTOP1 expression is inducible by Al3+ and H+ stress. However, although VuSTOP1 binds to the promoter of VuMATE1, the inconsistent tissue localization patterns of VuSTOP1 and VuMATE1 preclude VuSTOP1 as the major factor regulating VuMATE1 expression. In addition, when a protein translation inhibitor increased expression of VuSTOP1, VuMATE1 expression was inhibited. In planta complementation assay demonstrated that VuSTOP1 could fully restore expression of genes involved in H+ tolerance, but could only partially restore expression of AtMATE. We conclude that VuSTOP1 plays a major role in H+ tolerance, but only a minor role in Al3+ tolerance. The differential transcriptional regulation of VuSTOP1 and VuMATE1 reveals a complex regulatory system controlling VuMATE1 expression.